Preparation and in vivo evaluation of nano sized cubosomal dispersion loaded with Ruta graveolens extracts as a novel approach to reduce asthma-mediated lung inflammation - Mohammad H. Alyami; Dalia I. Hamdan; Heba M.A. Khalil; Mohamed A.A. Orabi; Nora M. Aborehab; Nada Osama; Mai M. Abdelhafez; Abdulaziz Mohsen Al-Mahallawi; Hamad S. Alyami (Elsevier, 2024)
Asthma is a chronic disease affecting people of all ages. Asthma medications are associated with adverse effects restricting their long-term usage, demanding newer alternative therapies. This study aimed to investigate the anti-asthmatic properties of Ruta graveolens extract and its prepared nano-cubosomal dispersion (Ruta-ND). Firstly, the R. graveolens methanolic extract exhibited higher anti-inflammatory activity on Lipopolysaccharide (LPS)-activated BEAS-2B cells. To ensure best bioavailability and hence best cellular uptake, R. graveolens extract was loaded in nano-cubosomal dispersion (ND). Then, the anti-asthmatic effects of Ruta extract and ND were simultaneously evaluated in rats' model with ovalbumin-induced allergic asthma. R. graveolens extract and Ruta-ND subsided asthma score and improved lung function by restoring FEV1/FVC ratio to the expected values in control rats. Also, it showed strong antioxidant and anti-inflammatory activities manifested by lowering levels of malondialdehyde (MDA), IL-4, IL-7, TGF-β, and Ig-E, and increasing levels of superoxide dismutase (SOD) and INF-γ in bronchoalveolar lavage fluid. Our research findings also indicate autophagy induction and apoptosis inhibition by Ruta extract and Ruta-ND. Finally, the HPLC MS/MS phytochemical profiling of R. graveolens extract evident production of various alkaloids, flavonoids, coumarins, and other phenolics with reported pharmacological properties corresponding to/emphasize our study findings. In conclusion, R. graveolens exhibited promise in managing Ova-induced allergic asthma and could be developed as an alternative anti-allergic asthma drug.